Mitigation measures for barriers to Great Plains fish migration - Ficke, Ashley D., author; Myrick, Christopher, advisor; Bestgen, Kevin, committee member; Fausch, Kurt, committee member; Thornton, Christopher, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.